The Influence of Customer Involvement and Social Networking Sites on Innovation Performance - Nugraha, Sukma; Ridwan, Muhammad; Hamdani, Nizar Alam (Entrepreneurship Faculty, Universitas Garut, 2023)
This research discusses how customer engagement and social networking sites influence business performance. The population in this study were buyers or connoisseurs of dodol products in the Garut Regency. This type of research is quantitative research with a descriptive approach. The sample used was 97 dodol customer respondents in Garut Regency who were distributed using a questionnaire via Google Form media and then processed using the SPSS statistics 26 and SmartPLS 3 applications using purposive sampling. The analysis used in this research is the outer model test, inner model test, and hypothesis test, which are carried out using the R-square value, direct effect, bootstrap, and t-statistic methods. This research aims to determine the influence of customer involvement on innovation performance and the influence of social networking sites on innovation performance. The results of this research state that customer involvement influences innovation performance, which influences 64.03%, and social networking sites influence innovation performance, which influences 21.96%. The results of these two hypotheses show that the variables can control each other with a high value at that time. So it can be concluded that there is an influence of customer involvement on the innovation performance of dodol products in Garut Regency as well as enthusiasm (enthusiasm), attention (attention), absorption (absorption), interaction (interaction) and identification (identification) which are very supportive of several indicators in performance innovation in dodol products in Garut Regency and that there is an influence of social networking sites on the innovation performance of dodol products in Garut Regency as well as social communities, social media platforms and social media .